Self-esteem and perfectionism versus procrastination - Lipińska-Grobelny, Agnieszka; Bednarek, Karolina (Kwartalnik Naukowy Fides et Ratio, 2021)
The purpose of this study was to examine whether levels of self-esteem and perfectionism are related to passive and active work postponement. The study was conducted among 325 young adults (219 females and 106 males). The following tools were used: New Active Procrastination Scale (NAPS), General Procrastination Scale (GPS), Polish Questionnaire of Adaptive and Maladaptive Perfectionism (KPAD), Rosenberg Self-Esteem Scale (SES). The results indicate that active procrastination is negatively related to self-esteem and maladaptive perfectionism, and positively related to adaptive perfectionism. Passive procrastination positively correlates with self-esteem and maladaptive perfectionism, and negatively with adaptive perfectionism. The obtained data deepen the knowledge on the determinants of procrastination, which is worth considering from two perspectives - positive and negative.